Activité antibactérienne des feuilles de l’olivier Olea europea L. subsp. europaea var. sylvestris lehr - Kharous, Adel; Benazzouzi, Youness (My University, 2020)
Our work aims to know the evaluation of the antibacterial effects of extract of olive leaves against seven pathogenic strains: Staphylococcus aureus ATCC 33862, Bacillus cereus ATCC10876, Proteus mirabilis ATCC 35659, Escherichia coli ATCC 25922, Klebsiella pneumoniae ATTC, Candida albicans ATCC 10231, Pseudomonas aeruginosa ATCC 27853 by AWDT agar well diffusion method and Minimum Inhibitory Concentration (MIC). The evolution of this antibacterial effect shows that the most interesting zone of inhibition measured on the Staphylococcus aureus strain ATCC 33862, while the lower diameter of inhibition (08 mm) by the strain Pseudomonas aeruginosa ATCC 27853. Classification of the strains By order of decreasing sensitivity : Staphylococcus aureus ATCC 33862 inhibition diameter of 30 mm, Bacillus cereus ATCC10876 of inhibition diameter of 25 mm, Proteus mirabilis ATCC 35659 diameter of 14 mm, Escherichia coli ATCC 25922 diameter inhibition of 12 mm., Klebsiella pneumoniae ATTC 13883 diameter of 10 mm, diameter of 09 mm for Candida albicans ATCC 10231, Pseudomonas aeruginosa ATCC 27853 a diameter of 08 mm. The highest recorded MIC values are 100 μg / mg for Staphylococcus aureus ATCC 33862, while the lowest recorded MIC is 25 μg / ml for Klebsiella pneumoniae ATTC 13883.
Keywords: Olea europea; Antimicrobial activity; pathogenic strains; MIC.